Export of Fiat Automobiles Serbia into Russian market: Opportunities and risks - Rakita Branko; Marković Dušan; Arsić Stefan (Ekonomski Pogledi, 2014)
Five years ago FIAT car company acquired Zastava Automobili manufacturing plant, by the agreement with the Government of the Republic of Serbia, and established FAS company (FIAT Automobiles Serbia). FIAT-Zastava Automobili acquisition has been the largest foreign direct investment (FDI) in Serbian industrial sector. This acquisition is a part of FIAT's going global strategy. In FIAT's global strategy FAS was initially planned to produce C class models for European market. Demand for automobiles in EU reduced dramatically due to debt crisis deepening, so FIAT is seeking alternative markets for FAS vehicles. Penetration into Russian market is considered an alternative, and the possible expansion of the goods list covered by the Free Trade Agreement between Serbia and Russia to automobiles would facilitate its achievement. This paper deals with Russian car market growth trends and how multinational companies (MNC) operate in markets with quiet inefficient institutions. Potential competitive advantages, as well as risks involved in FIAT's expansion into Russian market will be analyzed in this paper. The risks mean that currently FIAT takes a negligible share of Russian market so a deeper penetration would imply additional financial investments and development of the lacking intangible resources essential for doing business in emerging markets with inefficient institutions.